2018
DOI: 10.1002/hed.25356
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes in patients with 1‐cm to 4‐cm differentiated thyroid carcinoma according to extent of thyroidectomy

Abstract: Background: Recent guidelines advocate unilateral thyroidectomy for low-risk 1-cm to 4-cm differentiated thyroid cancer (DTC). This study was designed to examine the association between the extent of thyroidectomy and oncologic outcomes in patients with 1-cm to 4-cm DTC. Materials and Methods: From April 1978 to December 2011, 16 057 patients with DTC underwent thyroidectomy at Yonsei University Hospital. Among them, 5266 (32.8%) patients were classified as having 1-cm to 4-cm DTC and were enrolled in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…1). Table 1 summarizes the outcomes of the 14 studies that were ultimately included in the analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Two studies investigated the impact of prophylactic central neck dissection in hemithyroidectomy using a comparative method [11,19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Table 1 summarizes the outcomes of the 14 studies that were ultimately included in the analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Two studies investigated the impact of prophylactic central neck dissection in hemithyroidectomy using a comparative method [11,19].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies investigated the impact of prophylactic central neck dissection in hemithyroidectomy using a comparative method [11,19]. Six investigations compared oncological results between total thyroidectomy and hemithyroidectomy in various subjects; however, only the data regarding hemithyroidectomy were included in the present study [10,12,13,20,21,23]. Others compared recurrence according to various factors among patients who underwent hemithyroidectomy [14][15][16][17][18]22].…”
Section: Resultsmentioning
confidence: 99%
“…The initial search resulted in a total of 7203 records. After removal of 2080 duplicates and screening of all titles and abstracts, a total of 68 papers were assessed in full text for inclusion, after which 58 were excluded, resulting in a total of ten studies [18][19][20][21][22][23][24][25][26][27] for analysis ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…2). Median time to recurrence was reported in four studies 19,[23][24][25] and ranged from 3⋅58 to 5⋅62 years. The majority of studies defined recurrence as proven by cytology and/or pathology ( Table S4, supporting information).…”
Section: Recurrencementioning
confidence: 99%
“…Mendelsohn et al showed that after controlling for tumor size, multivariate analysis revealed no survival difference between TT versus TL [ 41 ]. Other studies, not meeting the selection criteria for this meta-analysis, also report excellent long-term clinical outcomes in selected low-risk patients [ 46 , 48 , 49 , 50 , 51 , 52 ]. Our meta-analysis supports the lack of a significant effect of the extent of surgery on the survival outcome in the low-risk patient category amenable for TL according to the ATA guidelines.…”
Section: Discussionmentioning
confidence: 97%